Level of Student Satisfaction with the Performance of Electrochemical Analysis Practice Instructors - Moh Hayat; Arif Muchyidin; Udin Asrorudin (MASI Mandiri Edukasi, 2025)
This study aims to analyze student satisfaction with instructors' performance in Electrochemical Analysis Practice at AKA Bogor Polytechnic. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire based on the Likert scale, which was distributed to 23 students who had completed the course. Data analysis is carried out descriptively with frequency and percentage calculations, then converted into qualitative information. The study results showed that the overall level of student satisfaction was in the